Recovery of mono-ethylene glycol by distillation and the impact of dissolved salts evaluated through simulation of field data - Zaboon, S.; Soames, A.; Ghodkay, V.; Gubner, Rolf; Barifcani, A. (Elsevier Inc., 2017)
This study was conducted to investigate the operation of a packed distillation column and analyse its performance during the separation of mono-ethylene glycol from water. The column was designed and constructed by the Curtin Corrosion Engineering Industry Centre (CCEIC) and operated in collaboration with a reputable oil company to generate experimental field data. A secondary investigation was then performed into the impacts of dissolved salts within the rich MEG feed upon the purity of the lean MEG product. It was observed through application of the FUG shortcut distillation design equations that six equilibrium stages were required to attain the experimental separations reported under continuous operation of the column. It was further determined that the packing utilised within the column had a Height Equivalent to a Theoretical Plate (HETP) of approximately 0.34 m when no dissolved salts were present corresponding to an estimated packing height of approximately 1.7 m. The impact of dissolved salts upon the performance of the column was evident through lower lean MEG purities observed during experimental operation of the column in comparison to salt free trials. The reduction in column performance was reaffirmed by Aspen HYSYS and Aspen Plus simulations of the field data, where salt trials resulted in lean MEG purities noticeably less than corresponding salt free experimental trials and simulated predictions. Overall, it was observed that the presence of dissolved salts during operation led to a reduction in MEG mass fraction of the final lean MEG product by on average 7.2%. The impact of dissolved salts on lean MEG purity was successfully predicted by Aspen Plus simulation with an average accuracy of 1.61% through the inclusion of monovalent salt cations using the ELECNRTL equation of state with modified binary parameters. The reduction in lean MEG purity was attributed to boiling point elevation of the MEG-Water solution and the impact of the dissolved salts on the systems vapour liquid equilibrium.